Direct involvement of p53 in programmed cell death of oligodendrocytes. - Eizenberg, O (1995)
A covalent dimer of interleukin (IL)-2, produced in vitro by the action of a nerve-derived transglutaminase, has been shown previously to be cytotoxic to mature rat brain oligodendrocytes. Here we report that this cytotoxic effect operates via programmed cell death (apoptosis) and that the p53 tumor suppressor gene is involved directly in the process. The apoptotic death of mature rat brain oligodendrocytes in culture following treatment with dimeric IL-2 was demonstrated by chromatin condensation and internucleosomal DNA fragmentation. The peak of apoptosis was observed 16-24 h after treatment, while the commitment to death was already observed after 3-4 h. An involvement of p53 in this process was indicated by the shift in location of constitutively expressed endogenous p53 from the cytoplasm to the nucleus, as early as 15 min after exposure to dimeric IL-2. Moreover, infection with a recombinant retrovirus encoding a C-terminal p53 miniprotein, shown previously to act as a dominant negative inhibitor of endogenous wild-type p53 activity, protected these cells from apoptosis.